Inventory tracker with estimation - Beh, Wei Jun (2024)
In today's rapidly evolving business landscape, small businesses must embrace digital transformation to remain competitive. Inventory management is a critical yet often overlooked aspect, and many small businesses still rely on traditional pen-and-paper inventory management. This challenges companies to maintain accurate and up-to-date inventory levels, reducing efficiency and accuracy. To address this challenge, the "Inventory Tracking and Estimating" project proposes the development of a user-friendly mobile application designed to simplify inventory management for small businesses. The app leverages the Flutter framework for cross-platform mobile app development, providing a solution that can be accessed through smartphones. By replacing traditional pen and paper methods, the app digitizes the inventory management process, increasing accuracy and efficiency. Key features include inventory tracking, estimation algorithms based on historical data, and integration with communication tools like WhatsApp for seamless order management. The project uses a structured approach that includes planning, analysis, design, implementation and maintenance phases to ensure the application meets the specific needs of the small business. Since its development, the app has been thoroughly tested and has successfully demonstrated its core functionalities, including user authentication, transaction management, and inventory operations. The testing confirmed that the system is both scalable and reliable, providing a robust solution for small businesses with limited resources. Overall, the project offers a comprehensive solution that modernizes inventory management for small businesses, empowering them to operate more efficiently and adapt to the competitive market through digital innovation.